Rehabilitation of cement concrete pavement structures at Bratislava airport - Andrea Zuzulová; Dominika Glasnáková (Acta Polytechnica CTU Proceedings, 2025)
The pavements on the movement areas of the airport are a specific group of pavements, due to their characteristics, different traffic loads and the time constraints for their repairs and maintenance. Increased requirements are on the proposed repairs already from the mentioned time point of view, as well as on the lifetime, which makes these repairs more economically demanding. Maintaining the optimal and efficient operation of the airport is primarily achieved by appropriate rehabilitation and innovation of the necessary parts of the airport. This was also subject to the replacement of the axial strips of the runway, part of the apron and the junction of the runways. The paper deals with the preparation, technical solution and implementation of these repairs with a description of individual technical parameters.